Determinants of economic well-being among Sri Lankan coconut growers and the role of technology adoption - Thilal, Wijekoon Kuruppu Mudiyanselage Rusitha (2022)
Economic well-being level of Sri Lankan coconut growers’ is still low due to lower level of income, and leads to greater financial vulnerabilities. Hence, Ministry of Plantation is establishing national programs to increase the economic well-being of Sri Lankan coconut growers which refers to an economic status that has sustainably adequate economic resources to live a comfortable life. However, the concept of economic wellbeing is still in its infancy, with only a few models established for the developing countries. Therefore, it is identified as a goal of public policy, and argued that governments should use measures of economic well-being rather than of economic activity to assess national progress and formulate policies accordingly. Therefore, identification of the determinants of economic well-being is the prerequisite to get the appropriate decisions. Hence the major objective of the current study is to examine the major determinants of economic well-being of the coconut growers in Sri Lanka. Further, it examined the mediation effect of technology adoption on the relationship between the economic well-being determinants and economic well-being, and moderation effect of age on the relationship between technology adoption and economic well-being. The theoretical framework was developed based on the reasoned linkages between the variables and the theoretical foundations of the Family Resource Management Theory, Theory of Planned Behavior, and Unified Theory of Acceptance and Use of Technology. A cross-sectional survey method using questionnaire form was conducted in the selected areas in Sri Lanka, and a sample of 416 respondents at the Coconut Triangle was initially selected using the multi-stage random sampling method. The data collected were analyzed descriptively and inferentially using SPSS and Smart- PLS software. The basic analyzes such as, descriptive analyzes were performed by using SPSS, while the inferential analyzes for instance, path coefficient analyzes, mediation analyzes, and moderation analysis were carried out by PLS-SEM. The results discovered that there were significant relationships between nine determinants (financial knowledge, financial behavior, money attitude, family members, growers’ educational qualifications, growers’ years of experience, willingness to change, effort expectancy, and technology adoption) and economic well-being. The 93.5% variance of economic well-being was explained by the significant determinants of the model. Moreover, the effects of the above determinants on the variable; technology adoption were also examined. Based on the results seven determinants; financial knowledge, subjective norms (i.e. family members, peer growers, and Coconut Development Officers), willingness to change, performance expectancy, subsidies/loans were detected to have a significant positive effects on growers’ agricultural technology adoption, and 94% of the variance of technology adoption was clarified. Furthermore, the technology adoption mediated the relationships between eight economic well-being determinants, such as, financial knowledge, money attitude, family members, peer growers, Coconut Development Officers, willingness to change, performance expectancy, subsidies/loans, and economic well-being. As for the moderator of age, the result displayed a nonmoderated effect with regards the technology adoption and economic well-being relationship. Moreover, a significantly higher (p<0.01) economic well-being was found for technology adopted coconut growers than non-technology adopted coconut growers. This study has contributed to the existing body of knowledge by providing support for the importance of the economic well-being determinants towards the economic wellbeing, based on theoretical reasoning and empirical findings. Further, understanding the paths that lead to better individual economic well-being has the potential to aid in successful policymaking and curriculum design to assist individuals’ efforts to achieve greater economic well-being.